Analysis of evidence on techno-stress, factors, implications, and mitigation strategies in health students. - Urrejola Contreras, Gabriela; Herrera-Lillo, Antonieta (Spanish Journal of Medical Education, 2025)
Technology has been widely integrated into health sciences education, especially during the pandemic, fostering digital learning. However, studies reveal challenges such as limited technological skills, technostress, and difficulties in critical tasks. Factors such as age, gender, and motivation influence the use of mobile devices for learning. Technostress, with its negative effects on academic performance, requires strategies to mitigate its impact, particularly among health students. The objective was to analyze the available evidence on technostress, its triggers, and mitigation strategies. A literature search was conducted for publications between 2019 and 2024, available in English and Spanish. The databases consulted included Scopus, PubMed, EBSCO, and ERIC, along with an additional free search. A total of eight articles were included in this integrative review. The methodological assessment criteria suggested by the Equator Network were followed. Technostress, present among health sciences students, arises from excessive use and poor management of technology. Overload, technological complexity, and constant availability expectations intensify it, affecting well-being, academic performance, and mental health. To address it, strengthening computer self-efficacy, implementing institutional support, and adopting personal strategies such as digital disconnection, relaxation, and balanced technology use management are recommended. Proper strategies can turn this challenge into academic growth, and a comprehensive approach that includes institutional support, digital training, teacher adaptation, and healthy habits can mitigate the impact and promote student resilience.